(untitled) (Global Journal of Science Frontier Research, 2023)
In a previous article the Cydonian Hypothesis was proposed, where it was hypothesized that what appeared to be strange landforms seen in orbital Mars Viking imagery, were, in fact, eroded archeology from an extinct, stone-age or early bronze-age, humanoid culture indigenous to Mars. It was the simplest hypothesis that could be formed, for the interpretation of the objects as artifacts, based on the data then available. Based on estimates of the ages of the terrains where these objects were found on Mars, approximately 1/2 billion years old, such a hypothetical humanoid culture was considered to be a completely independent biological development on our own culture on Earth. This culture, termed the Cydonians, was hypothesized to have developed and existed in a past period of Earth-like conditions on Mars. Analysis of new imagery, from recent probes, obtained at Cydonia Mensa and Galaxias Chaos, strongly supports the original Cydonian Hypothesis. Given the apparent catastrophic climate change on Mars from its past Earth-like state and Fermi’s Paradox: the unexpected silence of the cosmic neighborhood, it is recommended that a human Mars mission to these two sites be mounted immediately by the ISS (International Space Station) consortium to gain knowledge of this Cydonian Culture and the reasons for its demise.